Reviewing self-injury: Implications for the study of self-injury and suicidal behaviour in Malaysia - Thompson, H.; Hasking, Penelope (Penerbit Universiti Kebangsaan Malaysia, 2009)
Self-injury is a significant predictor of future self-harm and suicide, and is associated with significant psychological morbidity. However, despite an apparent increase in prevalence, very little research on this behaviour has been conducted within Malaysia. This paper reviews the definitional issues pertinent to the study of self-injury including the need to adopt a consistent nomenclature for the behaviour, separate self-injury which occurs with and without suicidal intent, and to address role of culture in defining self-injurious behaviour. A review and critique of research exploring the prevalence, function, aetiology, and correlates of self-injury across both clinical and community samples is provided. Finally, in light of the current international knowledge regarding self-injurious behaviour, recommendations to guide future research in Malaysia are proposed.